Biomarkers in Remission According to Different Criteria in Patients with Rheumatoid Arthritis - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2015)
Objective. Remission is the primary aim in the treatment of patients with rheumatoid arthritis (RA). In this study, we aimed to evaluate biomarker profiles of patients in remission by different criteria and compare these profiles with controls. Methods. Serum levels of calprotectin, interleukin 6 (IL-6), type II collagen helical peptide, C-terminal crosslinking telopeptide of type I collagen generated by matrix metalloproteinases (ICTP), matrix metalloproteinase 3 (MMP-3), resistin, and leptin were measured by ELISA in 80 patients. The patients were in Disease Activity Score at 28 joints with erythrocyte sedimentation rate (DAS28-ESR) remission, and had these characteristics: female/male 54/26, mean age 51.4 +/- 12.1 years, mean disease duration 11.4 +/- 8.1 years, rheumatoid factor positivity 68.7% (n = 55), anticyclic citrullinated peptide positivity 60.7% (n = 48). These patients were also evaluated for the American College of Rheumatology/European League Against Rheumatism (Boolean) and Simple Disease Activity Index (SDAI) remissions. Additionally, 80 age-, sex-, and comorbidity-matched individuals without rheumatic diseases were included in the study as controls. Results. At recruitment of 80 patients in DAS28 remission, 33 patients (41.2%) were found in Boolean remission and 39 patients (48.7%) were in SDAI remission. Serum MMP-3, ICTP, resistin, and IL-6 levels of the 80 patients in DAS28 remission were statistically significantly higher than the controls. Patients in Boolean and SDAI remissions had significantly higher serum ICTP, resistin, and IL-6 levels in comparison with the controls. Conclusion. The 3 commonly used remission criteria of RA are almost similar with regard to patients' biomarker levels. Biomarker profiles of patients may provide complementary information to clinical evaluation of remission and may help to determine the patients under the risk of progression.
Keywords: RHEUMATOID ARTHRITIS; BIOMARKERS; REMISSION CRITERIA; I COLLAGEN DEGRADATION; DISEASE-ACTIVITY; SERUM-LEVELS; CLINICAL REMISSION; SYNOVITIS; CARTILAGE; RECEPTOR; LEPTIN; OSTEOARTHRITIS; INTERLEUKIN-6